Judges' Code of Ethics in Deciding Cases - Farly Lumopa; Zaenal Arifin (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Judges play a vital role in upholding justice and public trust within the judicial system. This study examines the importance of the Judges' Code of Ethics in Indonesia, emphasizing its influence on the accountability and integrity of judicial decisions. The primary objectives are to analyze how the code serves as a guideline for judges and to assess its impact on public confidence in the legal system. Utilizing a normative juridical research method, the study relies on both primary and secondary legal materials, including legislative documents and case studies. The research involves a comprehensive literature review and a legislative approach to understand the ethical standards expected of judges in their professional conduct. The findings reveal that adherence to the Judges' Code of Ethics is crucial for maintaining impartiality, avoiding conflicts of interest, and ensuring fair trial processes. Ethical violations can significantly undermine public trust, leading to skepticism regarding judicial impartiality and the effectiveness of the legal system. The study highlights that judges must conduct themselves with integrity, uphold the principles of justice, and avoid any actions that could compromise their role. In conclusion, the Judges' Code of Ethics not only serves as a regulatory framework for judicial behaviour but also acts as a foundation for public confidence in the judiciary. For the legal system to function effectively, it is imperative that judges adhere to these ethical standards, ensuring that their decisions are perceived as fair and just.